Survei Kepuasan Dosen Terhadap Layanan Program Studi S1 Ekonomi Pembangunan - Lavlimatria Esya; Syofriza Syofyan (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
The aim of this research was to determine the level of lecturers' satisfaction with the quality of the Undergraduate Development Economics Study service program, Faculty of Economics, Trisakti University, and to look for the determining factors of lecturer satisfaction, so that they can find out the dominant factors in the quality of the Undergraduate Development Economics Study service program, Faculty of Economics, University. Trisakti. Research data was obtained by distributing a lecturer questionnaire with 32 questions via online media (Google Form). The results show that the service satisfaction of the study program for Lecturers and Education Personnel of the Development Economics Undergraduate Study Program, Faculty of Economics and Business, Trisakti University is on average good and very good from these aspects: (1) competency development, (2) career development, ( 3) development of research and scientific work, (4) development of community service, (5) additional development and welfare. The implications of these results indicate that lecturers within the scope of the Development Economics Study Program are satisfied with the services provided by the study program, however, because the level of satisfaction is not all very good, the study program in the future needs to improve services.